Peran Motivasi Intrinsik dalam Meningkatkan Kesadaran Menjaga Hafalan Al-Qur’an Mahasiswa Universitas PTIQ - Agus Nur Qowim; Nur Afif (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Awareness of maintaining Al-Qur’an memorization is the key to success in the comprehensive Al-Qur’an memorization exam for students at PTIQ University Jakarta. Awareness of maintaining Quran memorization is closely related to internal motivation, which will direct all activities to achieve goals, through persistent efforts to repeat what has been memorized. This study used qualitative methods. This study concluded that internal motivation is the most important factor in fostering awareness of maintaining Al-Qur’an memorization. Internal motivation will encourage and direct students to make maximum efforts in maintaining Al-Qur’an memorization. Cultivating awareness of maintaining Al-Qur’an memorization can also be done by understanding, reflecting on, and analyzing hadiths that contain the virtues of memorizing the Al-Qur’an and the obligation to maintain Al-Qur’an memorization.